Making Ends Meet - Mary N. Harrison (EDIS)
There are things you can do to stretch you dollars. This document contains steps you can take to save money and build a good future. This document is FCS5235-01, one of a series of the Department of Family, Youth and Community Sciences, UF/IFAS Extension. Original publication date: May 2002. Revised: December 2005.